Systemic movement of FT mRNA and a possible role in floral induction - Jackson, Stephen; Hong, Yiguo (Frontiers in Plant Science, 2012)
FLOWERING LOCUS T (FT) protein is known to be part of the mobile flowering inducing ‘florigen’ signal in plants, but it may not be acting alone. This article reviews the data that FT mRNA can also move systemically throughout the plant and into the shoot apical meristem (SAM) independently of the FT protein. There is a promotion of flowering when increased levels of virally expressed FT mRNA are present together with endogenously produced FT protein in inducing conditions, even if the additional FT mRNA is non-translatable and thus not increasing the overall levels of FT protein. A specific sequence, or ‘zip code’ of the FT mRNA is required for systemic movement and this sequence binds a specific protein(s) in plant extracts. This raises the possibility the FT mRNA may be moving systemically through the plant and into the SAM as an RNA-protein complex, whether FT protein is also a component of this mobile complex remains to be determined.